2003
DOI: 10.2136/sssaj2003.1524
|View full text |Cite
|
Sign up to set email alerts
|

Management and Soil‐Quality Effects on Fertilizer‐Use Efficiency and Leaching

Abstract: outcomes to readily measurable parameters, we should be able to better optimize management within different We tested the hypothesis that particulate organic matter (POM) regions and cropping systems. and aggregate dry mean weight diameter (DMWD) are related to This work follows up on previous findings suggesting fertilizer-use efficiency (FUE) and leaching susceptibility. Soil cores measures of POM and aggregation are particularly good (15 cm diam. by 50 cm depth) were collected from 12 farm fields representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 54 publications
3
29
2
Order By: Relevance
“…Several biological indicators of soil quality have been proposed because they are thought to be integrative variables, sensitive to changes in soil degradation or improvement [27][28][29][30]. However, we are interested in mapping soil quality on the landscape level to monitor change or implement remediation, and there are several problems associated with the use of only biological indicators over field to landscape scales.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological indicators of soil quality have been proposed because they are thought to be integrative variables, sensitive to changes in soil degradation or improvement [27][28][29][30]. However, we are interested in mapping soil quality on the landscape level to monitor change or implement remediation, and there are several problems associated with the use of only biological indicators over field to landscape scales.…”
Section: Discussionmentioning
confidence: 99%
“…Organic agriculture is defined as having no synthetic inputs, but organic farms may or may not practise the full suite of cultivation techniques characterizing sustainable agriculture [21,25]. Although the terms 'organic' and 'sustainable' agriculture are not equivalent, studies of organic agriculture have revealed better performance than conventional systems on some (but not all) sustainability metrics, including species richness and abundance, soil fertility, nitrogen uptake by crops, water infiltration and holding capacity, and energy use and efficiency [26][27][28][29][30][31][32]. Here, we provide the most comprehensive calculation of the yield gap between organic and conventional agriculture, building on the work of others [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, Crowder and Reganold [103] found that though organic yields were lower than industrial, organic price premiums only had to be 5%-7% for industrial and organic farms to have the same profit, although currently premiums far surpass the break-even-point at 29%-32% [103]. Studies of organic agriculture have also revealed better performance than industrial systems in lowering negative externalities and increasing positive ones through enhancing species richness and abundance, soil fertility, nitrogen uptake by crops, water infiltration and holding capacity, and energy use and efficiency [25,[27][28][29][30][31][32]44].…”
Section: Economic Viabilitymentioning
confidence: 99%
“…These landscapes are designed to support a greater variety of wildlife, some of which would help to pollinate crops and control pests. Measures to spatially and temporally diversify farms to mimic nature, collectively known as diversification techniques or agro-ecological, ecologically-intensive, biologically diversified or regenerative farming systems, are shown to be less environmentally and socially damaging than industrial in terms of limiting pesticide exposure, soil erosion and biodiversity loss, while enhancing nutrient, energy and water efficiency (e.g., [1,[22][23][24][25][26][27][28][29][30][31][32][33]). …”
Section: Introductionmentioning
confidence: 99%